1998
DOI: 10.1074/jbc.273.46.30695
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Cloning of an S-Adenosylmethionine-dependent 3-Amino-3-carboxypropyltransferase in Nocardicin Biosynthesis

Abstract: S-Adenosylmethionine:nocardicin 3-amino-3-carboxypropyltransferase catalyzes the biosynthetically rare transfer of the 3-amino-3-carboxypropyl moiety from S-adenosylmethionine to a phenolic site in the ␤-lactam substrates nocardicin E, F, and G, a late step of the biosynthesis of the monocyclic ␤-lactam antibiotic nocardicin A. Whereas a number of conventional methods were ineffective in purifying the transferase, it was successfully obtained by two complementary affinity chromatography steps that took advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 90 publications
(88 reference statements)
0
50
0
Order By: Relevance
“…6). Although rare, SAM-dependent 3-amino-3-carboxypropyl transferases are known to participate in other bacterial syntheses, e.g., in the biosynthesis of the antibiotic nocardicine (44).…”
Section: Discussionmentioning
confidence: 99%
“…6). Although rare, SAM-dependent 3-amino-3-carboxypropyl transferases are known to participate in other bacterial syntheses, e.g., in the biosynthesis of the antibiotic nocardicine (44).…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of oxidized supernatants were analyzed by TLC as previously described (30). Fractions that contained the highest levels of the activity that converted arsenite to methylated and dimethylated products were pooled and applied to a column of an S-adenosyl-Lhomocysteine-Sepharose affinity gel that was prepared by the method of Reeve and co-workers (31). The chromatographic gel was fully equilibrated with 50 mM Na phosphate buffer containing 5 mM GSH, 1 mM DTT, and 5% (v/v) glycerol, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…1). The side chain is attached by Nat from AdoMet, to initially present the L-configuration (16). Wilson et al (46) reported a cell-free system from N. uniformis containing both transferase, and epimerase activities.…”
Section: Analysis Of Nocj-mentioning
confidence: 99%
“…Reverse genetics techniques from the AdoMet-dependent 3-amino-3-carboxypropyl transferase (Nat) have allowed the nocardicin biosynthetic gene cluster to be identified and characterized from N. uniformis (16,17). Notably present in the cluster are two non-ribosomal peptide synthetases (NRPSs), genes required for generation of the non-proteinogenic amino acid p-(hydroxyphenyl)glycine, (17) nocL, which encodes a cytochrome P450 responsible for oxime formation in the nocardicins, (18) and nat providing the side chain AdoMet-dependent transferase.…”
mentioning
confidence: 99%